2022
DOI: 10.1017/s0950268822000267
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of inactivated SARS-CoV-2 vaccine (CoronaVac) on intensive care unit survival

Abstract: This study compared the course of COVID-19 in vaccinated and unvaccinated patients admitted to an intensive care unit (ICU) and evaluated the effect of vaccination with CoronaVac on admission to ICU. Patients admitted to ICU due to COVID-19 between 1 April 2021 and 15 May 2021 were enrolled to the study. Clinical, laboratory, radiological parameters, hospital and intensive care unit mortality were compared between vaccinated patients and eligible but unvaccinated patients. Patients over 65 years old were the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
2
6
1
Order By: Relevance
“…Desai et al 31 stated that the length of hospital and ICU stay in vaccinated patients was significantly shorter than that in the unvaccinated patients. This finding was in contrast with those declared by Sevinc et al, 8 who reported no difference. This could be attributed to the participants’ age, different vaccine types (CoronaVac of inactivated vaccines), or a different variant of COVID‐19.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Desai et al 31 stated that the length of hospital and ICU stay in vaccinated patients was significantly shorter than that in the unvaccinated patients. This finding was in contrast with those declared by Sevinc et al, 8 who reported no difference. This could be attributed to the participants’ age, different vaccine types (CoronaVac of inactivated vaccines), or a different variant of COVID‐19.…”
Section: Discussioncontrasting
confidence: 99%
“…The rapid progress of multiple vaccines with different platforms resulted in the development of a negative public attitude toward COVID‐19 vaccination; however, COVID‐19 vaccines have been highly effective in curtailing symptomatic and severe forms of COVID‐19 and its associated mortality 8 . Moreover, a modest reduction in vaccine effectiveness was observed against mild disease with some variants; however, its effectiveness against severe forms of disease remained high at least 6 months after immunization with two doses 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…But the sample size in this study was only 90, and the data were from COVID-19 patients over 65 years old. 16 …”
Section: Efficacymentioning
confidence: 99%